2016
DOI: 10.1002/anie.201606641
|View full text |Cite
|
Sign up to set email alerts
|

Stereospecific Synthesis of Alkenes by Eliminative Cross‐Coupling of Enantioenriched sp3‐Hybridized Carbenoids

Abstract: 1-Aryl-1,2-dialkylethenes were generated by a sequence of electrophilic substitution, 1,2-metalate rearrangement, and β-elimination initiated by the addition of enantioenriched α-(carbamoyloxy)alkylboronates to enantioenriched lithiated carbamates. The carbenoid stereochemical pairing [i.e., "like"=(S)+(S) or "unlike"=(S)+(R)] and the elimination mechanism (syn or anti), not substituent effects, determined the configuration of the trisubstituted alkene target. For example, (Z)-2,5-diphenyl-2-pentene was produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 36 publications
0
23
1
5
Order By: Relevance
“…Stereospecific trisubstituted alkene synthesis by eliminative cross-couplingofLi-and B-based carbenoids involving anti-mode elimination.C bO = i-Pr 2 NCO 2 ,B pin = B(OCMe 2 CMe 2 O). [74] Scheme 21. Stereospecific trisubstituted alkene synthesis by eliminative cross-coupling of Li-and B-based carbenoidsi nvolving syn-mode elimination.C bO = i-Pr 2 NCO 2 ,B neo = B(OCH 2 CMe 2 CH 2 O).…”
Section: Avignette On the Possibility Of Noncanonical Mechanismsmentioning
confidence: 76%
See 3 more Smart Citations
“…Stereospecific trisubstituted alkene synthesis by eliminative cross-couplingofLi-and B-based carbenoids involving anti-mode elimination.C bO = i-Pr 2 NCO 2 ,B pin = B(OCMe 2 CMe 2 O). [74] Scheme 21. Stereospecific trisubstituted alkene synthesis by eliminative cross-coupling of Li-and B-based carbenoidsi nvolving syn-mode elimination.C bO = i-Pr 2 NCO 2 ,B neo = B(OCH 2 CMe 2 CH 2 O).…”
Section: Avignette On the Possibility Of Noncanonical Mechanismsmentioning
confidence: 76%
“…[73] Although not conducted with the intention of making alkenes,t he findings of Matteson et al underscore the feasibility of as tereospecific olefin-forming cross-coupling reaction based on the combination of two different enantioenriched carbenoids.S uch ap rocess,w hich likewise exploits the differential reactivity of lithium-and boronbased carbenoids,w as successfully developed and recently disclosed by Blakemore and co-workers (Schemes 20 and 21). [74] Them ethod hinges on eliminative cross-coupling of an ucleophilic lithiated carbamate (e.g. 116)w ith an electrophilic a-carbamoyloxyboronate (e.g.…”
Section: Eliminative Cross-coupling Involving Boron-based Carbenoidsmentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Second, to obtain complete transfer of stereochemical information, the elimination process must proceed with very high stereospecificity. [11] The choice of vinylic leaving group (LG 1 )iscritical to controlling the selectivity in both of these key steps.W ewere attracted to selenium as we hoped that its relatively poor leaving group ability would enable it to act as aspectator group during the lithiation-borylation process and then, upon activation, to undergo elimination (Scheme 1C). Moreover,w eh ave recently shown that b-seleno boronic esters can undergo selective anti elimination in the presence of base or syn elimination upon oxidation to the corresponding selenoxide.…”
Section: Allenesareversatilefunctionalgroupsthatcanbeemployedmentioning
confidence: 99%